2014
DOI: 10.1136/medethics-2014-102229
|View full text |Cite
|
Sign up to set email alerts
|

Abandoning the dead donor rule? A national survey of public views on death and organ donation

Abstract: Brain dead organ donors are the principal source of transplantable organs. However, it is controversial whether brain death is the same as biological death. Therefore, it is unclear whether organ removal in brain death is consistent with the ‘dead donor rule’, which states that organ removal must not cause death. Our aim was to evaluate the public's opinion about organ removal if explicitly described as causing the death of a donor in irreversible apneic coma. We conducted a cross-sectional internet survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 16 publications
5
41
0
3
Order By: Relevance
“…This is not a new concept. 9,[18][19][20] The idea that living donation could be extended to patients in whom death is imminent 9 has been described previously. 18 Indeed, many patients have a significant desire to donate organs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is not a new concept. 9,[18][19][20] The idea that living donation could be extended to patients in whom death is imminent 9 has been described previously. 18 Indeed, many patients have a significant desire to donate organs.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, this practice would violate the dead-donor rule. [19][20][21] Conversion of DCD donors to living donors should be thought of in the context of several important considerations. Firstly, families (and, in some cases, patients themselves) have already made the decision to withdraw support.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most (but not all) participants who were willing to donate organs "after death" were also willing to donate in irreversible coma with organ retrieval causing death, and willingness to donate after death correlated positively with willingness to donate in irreversible coma. 84 This survey suggests that many members of the US public would support organ procurement in situations that violate the dead donor rule, casting doubt on the assertion that the dead donor rule is necessary to preserve trust and organ donation rates (at least in the USA), and …”
Section: The Dead Donor Rule and Consent For Organ Procurementmentioning
confidence: 99%
“…In a recent national survey, Nair-Collins et al 84 presented US residents (n=1,096) with a hypothetical scenario of organ procurement that violated the dead donor rule. A patient was described as being in an irreversible coma but biologically alive, and organ procurement was described as causing the biological death of the donor.…”
Section: The Dead Donor Rule and Consent For Organ Procurementmentioning
confidence: 99%
“…This ‘intuition’ is not, however, borne out in the sociological literature. One recent study, for example, found that about 70% of the US adults surveyed would donate their organs if they had devastating brain damage, even though the scenario clearly stipulated that removal of their organs would be the direct cause of their death 7. The point is not that everyone agrees with this view, but rather that honest discussion about the merits of the DDR is not a ‘non-starter’.…”
mentioning
confidence: 99%